Stigma, an important source of dissatisfaction of health workers in HIV response in Vietnam: a qualitative study - Pham Ha Nguyen; Protsiv Myroslava; Larsson Mattias; Ho Hien Thi; Vries Daniel H de; Thorson Anna (BMC, 2012)
Abstract Background Like in many other low- and middle-income countries, the recent development of an HIV epidemic in Vietnam has led to a growing need for prevention, treatment, care, and support services for people living with HIV (PLHIV). This puts greater demands on the national HIV services, primarily on health workers, which increases the importance of their job satisfaction and working conditions. This study describes health worker perceptions and explores the factors that influence job satisfaction and dissatisfaction of health personnel working on the HIV response in Vietnam. Spector's job satisfaction model was used as the theoretical framework for the study design and analysis. Methods The study employed a qualitative design with 7 focus group discussions and 15 semi-structured interviews with health workers, purposively selected from national and provincial organizations responsible for HIV services in 5 cities and provinces in Vietnam. Data were analyzed using a hybrid approach of theory-driven and data-driven coding and theme development using qualitative analysis software. Results HIV services are perceived by Vietnamese health workers as having both positive and negative aspects. Factors related to job satisfaction included training opportunities, social recognition, and meaningful tasks. Factors related to job dissatisfaction included unsatisfactory compensation, lack of positive feedback and support from supervisors, work-related stress from a heavy workload, fear of infection, and HIV-related stigma because of association with PLHIV. An adjusted Spector's model of job satisfaction for HIV service health workers was developed from these results. Conclusion This study confirmed the relationship between stigmatization of PLHIV and stigma experienced by staff because of association with PLHIV from families, colleagues, and society. The experiencing stigma results in additional work-related stress, low self-esteem, poor views of their profession, and lower income. The study shows the importance of actions to improve staff job satisfaction such as pay raises, supportive supervision, stress management, stigma reduction and workplace safety. Immediate actions could be the provision of more information; education and communication in mass media to improve the public image of HIV services, as well as improvement of workplace safety, therefore making health workers feel that their work is valued and safe.